Resilience: How Academics Stay After Multiple Psychological Contract Breaches - Yayan Firmansah; Zabeda Abdul Hamid; Suhaimi Mhd Sarif (University of Darussalam Gontor, 2023)
This qualitative phenomenological study explores the lived experiences of academics who have encountered multiple breaches in their psychological contracts within academic institutions. Through in-depth interviews with participants from diverse disciplines and career stages, the study investigates the coping mechanisms and adaptations in daily work activities employed by academics to navigate the emotional aftermath of psychological contract breaches. The findings reveal a multifaceted landscape of resilience, encompassing strategies such as seeking social support, engaging in professional development, utilizing creative outlets, and intentionally cultivating autonomy. Furthermore, adaptations in daily work activities include reorienting research focus, innovating teaching methodologies, embracing interdisciplinary collaborations, and committing to continuous learning. Comparisons with existing literature underscore both consistent themes and novel dimensions, contributing to a nuanced understanding of academic resilience. The study concludes with actionable recommendations for institutions to support the well-being and resilience of academics, emphasizing the importance of autonomy, interdisciplinary collaboration, and reflective practices. Future research directions are also proposed to deepen our understanding of academic resilience in the face of evolving challenges within the contemporary academic landscape.